PENGARUH GAYA HIDUP, LABEL HALAL, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DI GERAI STARBUCKS PADA GENERASI Z DI DAERAH ISTIMEWA YOGYAKARTA - Miswanto Miswanto; Izza Salsabila; Titik Kusmantini (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
This study aims to examine the effect of lifestyle, halal labels, and prices on purchasing decisions at Starbucks outlets in Generation Z in the Special Region of Yogyakarta. The population used in this study is Generation Z who is in the Special Region of Yogyakarta and who make purchases at Starbucks outlets, who are at least 15 years old and a maximum of 25 years old. This study uses a quantitative approach and causal analysis technique. The sampling technique uses non-probability with purposive sampling. The findings of this study are Lifestyle, Halal Label, and Price has a positive effect on purchasing decisions at Starbucks outlets in Generation Z in Yogyakarta Province. The theoretical implication of this study is that the findings of this study are expected to provide a view that lifestyle, halal labels, and prices can affect purchasing decisions at Starbucks outlets in Generation Z in the Special Region of Yogyakarta. The practical implication of this research is that the findings of this study are expected to provide input for Starbucks outlets to be able to continue to maintain quality and can increase understanding related to the importance of lifestyle, halal labels, and prices on purchasing decisions.